Plant Breeding for Water-Limited Environments - Blum , Abraham (New York : Springer, 2011)
This volume will be the only existing single-authored book offering a science-based breeder$1 (Bs manual directed at breeding for water-limited environments. Plant breeding is characterized by the need to integrate information from diverse disciplines towards the development and delivery of a product defines as a new cultivar. Conventional breeding draws information from disciplines such as genetics, plant physiology, plant pathology, entomology, food technology and statistics. Plant breeding for water-limited environments and the development of drought resistant crop cultivars is considered as one of the more difficult areas in plant breeding while at the same time it is becoming a very pressing issue. This volume is unique and timely in that it develops realistic solutions and protocols towards the breeding of drought resistant cultivars by integrating knowledge from environmental science, plant physiology, genetics and molecular biology.s
Include bibliographical references; Index 249-255p.
Keywords: Agriculture; Plant breeding; Water-limited environments; Botany